Implementación de drones con cámaras multiespectrales para optimizar el monitoreo y manejo de cultivos - Mora Parrales, Adonis Francisco (2025)
The implementation of drones with multispectral cameras in agriculture has transformed crop monitoring and management, allowing for more precise and efficient management. These unmanned aerial vehicles (UAVs) have been used to capture aerial images, but their ability to collect multispectral and thermal data has proven crucial for assessing crop health, detecting water stress, nutritional deficiencies, and diseases at early stages. Drones offer fast and accurate coverage of large areas, facilitating routine monitoring and making informed decisions about the use of resources such as water, fertilizers, and pesticides. Top models include the DJI Mavic 3 Multispectral and Phantom 4 Multispectral, which integrate advanced sensors and RTK positioning systems for centimeter-level accuracy. Research shows that these drones enable early detection of crop problems, irrigation optimization, and a significant reduction in the use of agrochemicals, improving the sustainability and profitability of agricultural operations. In addition, they facilitate the creation of crop health and vitality maps, helping in zoning and resource management. In conclusion, multispectral drones are essential tools for precision agriculture, offering detailed agronomic diagnoses and improving efficiency in the use of inputs. The methodology applied in this research was non-experimental bibliographic, using analysis of research articles, journals and current texts to synthesize and summarize the data collected on the use of drones in agriculture